(untitled) (Global Journal of Human-Social Science, 2023)
This work analyzes Hannah Arendt s essay The Crisis in Education published in the late 1950s intending to elucidate its central themes through the concepts presented in other works by the author This intention is a valuable initiative not only because of Arendt s qualifications who is one of the most influential thinkers of the 20th century but also because the essay has fostered research in the area of education and is frequently included in the bibliography of teacher training courses both in undergraduate and graduate levels due to the critical reflections it elaborates on the relationships between adults and children in modernity which includes the exchange between teachers and students